Investigation of aroma components obtained by HS-SPME (Headspace-solid phase microextraction) method of wild strawberry (Fragaria vesca L.) and strawberry (Fragaria x ananassa Duch.) fruits - Öz, Mehmet; Baltaci, Cemalettin; Fidan, Muhammed Said (My University, 2024)
Wild strawberries (Fragaria vesca) are in the category of non-wood forest products due to their unique fragrance, aroma, and natural ability to grow. In this study, aroma components of wild strawberry (Fragaria vesca) and strawberry (Fragaria x ananassa) fruits were determined by Headspace-Solid Phase Micro-Extraction technique combined with Gas chromatography-mass spectrometry (HS-SPME/GC-MS). In addition, it aimed to compare the results of both fruits with each other by chemical classification of the aroma components determined from wild strawberry and strawberry fruits. As a result of the HS-SPME/GC-MS analysis; 50 and 76 aroma components were determined in wild strawberry and strawberry fruits, respectively. The structure of aroma components was defined as 97.63% of wild strawberries and 98.26% of strawberries. The main components in the aroma compounds are 2-undecanone (10.38%), ?-decalactone (8.81%), and eugenol (7.14%) in wild strawberry fruit; nerolidol (29.44%), ?-decalactone (26.36%) and bisabolol oxide II (4.23%) were found in strawberry fruits. In addition, chemical classes of identified aroma compounds were determined as ester, terpene or terpenoid, fatty acids, aldehyde, and ketone classes in Fragaria vesca and Fragaria x ananassa fruits. When the results are examined, it is seen that strawberry fruits are found to be higher than wild strawberry fruits in terms of percentage of aroma components, number of aroma components, and percentage of dominant components.
Keywords: Fruit; Aroma components; HS-SPME/GC-MS; Wild strawberry